(untitled) (PIONIR: JURNAL PENDIDIKAN, 2025)
The rapid development of digital technology in education requires the strengthening of students’ digital literacy, particularly for students of the Elementary School Teacher Education Program (PGSD) as prospective primary school teachers. Digital literacy is not merely defined as the ability to read digital texts, but also the ability to understand, evaluate, and critically interpret information within Indonesian language learning contexts. This study aims to examine the effect of Indonesian language learning based on the Merdeka Curriculum on the digital literacy of PGSD students at the Faculty of Teacher Training and Education, Universitas Muhammadiyah Sumatera Utara (FKIP UMSU). This study employed a quantitative approach using a quasi-experimental design with a pretest–posttest control group. The research sample consisted of an experimental group and a control group selected through purposive sampling. The research instrument was a digital literacy questionnaire that had been tested for validity and reliability. Data were analyzed using descriptive statistics and an independent sample t-test. The results indicate a significant difference in digital literacy between PGSD students in the experimental and control groups. Indonesian language learning based on the Merdeka Curriculum was proven to be effective in improving students’ abilities to understand, evaluate, and interpret digital texts critically. These findings emphasize the importance of implementing the Merdeka Curriculum in Indonesian language learning to prepare digitally literate and adaptive prospective primary school teachers to meet the demands of 21st-century education. Keywords: digital literacy, Indonesian language learning, Merdeka Curriculum, PGSD